British Financial Experience 1790-1830 - Silberling, Norman J. (The Review of Economics and Statistics, 1919)
T HE monetary and financial events which attended the military operations carried on by Great Britain and her continental allies against the armies of France, between I793 and i8I5, have acquired at this time a special interest. The wars of the Napoleonic era present, in their political and economic aspects, numerous points of similarity to, as well as interesting points of contrast with, the great war of the past five years. An examination of some of the financial experiences of England during and immediately following this earlier period may be useful, not only in setting forth historical parallels and contrasts, but in furnishing valuable lessons for our own time. It is proposed to consider in this paper, certain aspects of the financial history of England for a period beginning just before the war and extending to the year I830, thus including the interval of recovery and return to normal conditions. The object of this study is primarily to bring together statistical data concerning currency, prices, the rate of interest, etc., which are available without elaborate research and special calculation. It is not intended to enter at any length into a causal inquiry or reasoned interpretation of the events disclosed, but rather to present the materials in clear and usable form, enabling comparison to be made between the various sets of data and laying a basis for further investigation.